Analisis Kesiapan Modul Ajar Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam - Mu'arif, Samsul; Wiqoyatin, Nafis; Zakiah, Umi Latifatuz; Ulya, Ailia Niswatul (AL-BURHAN, 2024)
This study aims to understand the readiness of teaching modules in implementing the Independent Curriculum in learning Islamic Religious Education at Madrasah Aliyah PIM Mujahidin Bageng Gembong Pati. The readiness of teaching modules is a determinant of success in learning. The research method used is descriptive qualitative. Data collection techniques using observation, interviews and documentation. While the data analysis technique is by reducing data, displaying data and verivicationts. . The results of this study revealed that the Readiness of the Teaching Module in Implementing the Independent Curriculum in Islamic Religious Education Learning, broadly speaking this is related to the readiness of teaching modules, the implementation of an independent curriculum and application in learning Islamic Religious Education. This research has an important meaning to achieve success in implementing an independent curriculum in Islamic religious education.Keywords: Readiness, Merdeka Curriculum, MA PIM Mujahidin